A new method for CDP input parameter identification of the ABAQUS software guaranteeing uniqueness and precision. Issue 2 (10th April 2017) - Labibzadeh, Mojtaba; Zakeri, Mojtaba; Adel Shoaib, Abdol
Abstract : Purpose: The purpose of this paper is to present a new method for determining the input parameters of the concrete damaged plasticity (CDP) model of ABAQUS standard software. The existing available methods in the literatures are case sensitive, i.e., they give different input parameters of CDP for a unique concrete class used in different finite element (FE) simulation of concrete structures. In this study, the authors attempt to introduce a new approach for the identification of the input parameters of the CDP model, which guarantees the uniqueness and precision of the model. In other words, by this method, the input parameters obtained for a specific concrete class with a unique characteristic strength can be used for FE simulation of the different concrete structures which were constructed by this concrete without the need to additional modifications raised from any new application. Design/methodology/approach: For the input parameter identification of the CDP model, different standard tests of plain concrete are simulated by the ABAQUS standard software. These test simulations are performed for various set of input parameters. In the end, those set of input parameters which represents the best curve fitting with the experimental results is chosen as the optimum parameters. Findings: By comparison of the FE simulation results obtained from the ABAQUS for two different concrete structures using the proposed input parameters for the CDP model with the experimental results, it was shown that the presented method for determining those parameters can guarantee the uniqueness and precision of the CDP model in simulation. Originality/value: The method described for determining the input parameters of the CDP model of the ABAQUS standard software has not been previously presented.